RA21 Considerations for Medical Libraries. Issue 2 (3rd April 2019) - Kraft, Michelle
Abstract: This article looks at the implications for hospital and medical libraries moving from traditional internet protocol validation or proxy access to access online resources to the newly proposed RA21 standard. Advantages and disadvantages of RA21 will be discussed as well as the implementation challenges for librarians.